Microbiology : Laboratory Manual - Cappuccino, James; Sherman, Natalie (Boston : Benjamin Cummings, 2011)
laboratory manual can be used with any undergraduate microbiology text-and now features brief clinical applications for each experiment, MasteringMicrobiology quizzes that correspond to each experiment and a new experiment on hand washing. Microbiology: A Laboratory Manual is known for its thorough coverage, descriptive and straightforward procedures and minimal equipment requirements. A broad range of experiments helps to convey basic principles and techniques. Each experiment includes an overview, an in-depth discussion of the principle involved, easy-to-follow procedures and lab reports with review and critical thinking questions. Ample introductory material and laboratory safety instructions are provided.
Includes Index 533-544p.
Keywords: Biology; Microbiology; Botany